2022
DOI: 10.3390/joitmc8040213
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Cashless Payment Systems for Business Transactions

Abstract: This paper examines the antecedents of cashless payment systems among businesses in Malaysia. The adoption of cashless payment systems by businesses has the potential to reduce the costs related to handling huge amounts of cash in the market and enhance transaction speed. Unfortunately, its current adoption in Malaysia is still small and very little is known about the factors. A seven-factor model based on the TOE framework was developed and tested. The partial least square (PLS) statistical approach was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Cashless healthcare facilities have stood out among these significant advances as bringing about a new era of effectiveness, convenience, and improved patient care with the development of an economy without cash is consistent with international initiatives to update financial institutions and promote accountability [13]. These digital solutions offer previously unheard-of benefits to both healthcare professionals and patients by streamlining transactions, reducing administrative difficulties, and encouraging a cashless society [14][15][16]. The advantages of cashless hospital services have transformed the healthcare sector [17,18].…”
Section: Introductionmentioning
confidence: 91%
“…Cashless healthcare facilities have stood out among these significant advances as bringing about a new era of effectiveness, convenience, and improved patient care with the development of an economy without cash is consistent with international initiatives to update financial institutions and promote accountability [13]. These digital solutions offer previously unheard-of benefits to both healthcare professionals and patients by streamlining transactions, reducing administrative difficulties, and encouraging a cashless society [14][15][16]. The advantages of cashless hospital services have transformed the healthcare sector [17,18].…”
Section: Introductionmentioning
confidence: 91%
“…Using SEM and 100 interviews with Indonesian students, Gunawan and Pulungan (2023) showed that financial technology payments and financial education have a major impact on consumer behavior. Rahman et al (2022) developed and tested a seven-factor model based on the TOE framework and a partial least squares (PLS) statistical approach and examined the antecedents of cashless payment systems among 200 small businesses in urban Malaysia that have access to the latest business payment technologies. The results showed that technological compatibility and competence have significant relationships with the adoption of cashless payment systems.…”
Section: Financial Literacy and Cashless Payment Awarenessmentioning
confidence: 99%
“…Therefore, compatibility for this study can be referred to as the degree to which e-commerce interacts with current firms' operations, as well as suppliers, customers, and competitors. Many studies (Eze et al, 2021;Gangwar et al, 2015;Nguyen et al, 2022;Rahman et al, 2022;Saffu et al, 2008) found that compatibility has a significant relationship with e-commerce adoption. Some other studies (Mahakittikun et al, 2021;Rahayu & Day, 2015), however, found that compatibility has a positive correlation with e-commerce adoption, but the correlation is not statistically significant.…”
Section: Technological Contextmentioning
confidence: 99%
“…Many studies suggested that e-commerce adoption may be influenced by technologyorganization-environment (TOE) factors (Eze et al, 2021;Feibert & Jacobsen, 2019;Gómez et al, 2022;Mahakittikun et al, 2021;Mujahed et al, 2022;Nguyen et al, 2022;Rahayu & Day, 2015;Rahman et al, 2022;Singeh et al, 2020). Most recent studies used TOE to measure the adoption of cloud computing (Mujahed et al, 2022), mobile banking (Mahakittikun et al, 2021), online retailing (Nguyen et al, 2022), cashless payment system (Rahman et al, 2022), and social media adoption (Eze et al, 2021). Therefore, this study needed to conduct an Exploratory Factor Analysis (EFA) to measure the reliability of the TOE instrument to be used in measuring e-commerce adoption on a more specific sample, which is Malaysian urban women entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%